2022
DOI: 10.32604/cmc.2022.024692
|View full text |Cite
|
Sign up to set email alerts
|

Modified Harris Hawks Optimization Based Test Case Prioritization for Software Testing

Abstract: Generally, software testing is considered as a proficient technique to achieve improvement in quality and reliability of the software. But, the quality of test cases has a considerable influence on fault revealing capability of software testing activity. Test Case Prioritization (TCP) remains a challenging issue since prioritizing test cases is unsatisfactory in terms of Average Percentage of Faults Detected (APFD) and time spent upon execution results. TCP is mainly intended to design a collection of test cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Anu and Sangwan [24] use the bat algorithm to research the TCP problem, and their results are greatly improved compared to traditional methods. Manar et al [25] designed an improved Harris Hawk optimization algorithm to improve prioritizing efficiency in many ways. Bajaj et al [26] used the discrete cuckoo search algorithm and introduced the adaptive strategy of asexual reproduction to reasonably improve the solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Anu and Sangwan [24] use the bat algorithm to research the TCP problem, and their results are greatly improved compared to traditional methods. Manar et al [25] designed an improved Harris Hawk optimization algorithm to improve prioritizing efficiency in many ways. Bajaj et al [26] used the discrete cuckoo search algorithm and introduced the adaptive strategy of asexual reproduction to reasonably improve the solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The multi-strategy Harris hawks optimization algorithm proposed by Abbasi et al [27] was used to solve the tapered roller bearing design problem, which confirmed the effectiveness of the algorithm under complex and variable constraints. The improved HHO algorithm proposed by Hamza et al [28] was used to optimize the prioritization of software testing, and the experimental results highlighted the high efficiency of the MHHO-TCP technique. The improved gradient-based HHO algorithm proposed by Abailigah et al [29] solves practical engineering problems, and uses the sine and cosine function to improve the convergence speed of the HHO algorithm, so that the improved algorithm can maintain excellent search ability in iterations.…”
Section: Introductionmentioning
confidence: 99%